Artificial Means of Reproduction and Our Understanding of the Family - Macklin, Ruth (The Hastings Center report, 1991)
The new reproductive technologies force us to rethink the concepts ‘mother,’ ‘father,’ ‘family.’ As we draw analogies to traditional patterns, we must distinguish between ethical and conceptual questions.